Still cooling after all these years: Meta-analysis of pre-clinical trials of therapeutic hypothermia for acute ischemic stroke. Issue 7 (July 2016) - Dumitrascu, Oana M; Lamb, Jessica; Lyden, Patrick D
Therapeutic hypothermia is the most potent neuroprotectant for experimental cerebral ischemia, illustrated in a 2007 meta-analysis published in this journal. To address recent therapeutic nihilism, we systematically reviewed recent experimental literature. Quality scoring showed considerable improvement in study design. Using several outcome measures in a variety of models and species, therapeutic hypothermia was protective compared with normothermia, with powerful and statistically significant normalized treatment effect sizes, in 60 papers comprising 216 comparisons. In the past 5 years, preclinical studies of ischemic stroke re-emphasize that therapeutic hypothermia is potently effective, justifying further development in larger human clinical trials.